A new Eleutherodactylus (Anura, Brachycephalidae) from the Venezuelan Guayana, and redescription of Eleutherodactylus vilarsi (Melin) - Barrio-Amorós, César L.; Molina, César R. (Zootaxa, 2006)
Eleutherodactylus aracamuni sp. nov. is described from the summit of Cerro Aracamuni, a granitic mountain in southern Amazonas state, Venezuelan Guiana. The new species is easily distinguished from other Guianan Eleutherodactylus by the absence of vomerine teeth, notched finger and toe discs, and its yellowish green coloration in life. It appears to be closely related to E. cavernibardus. Eleutherodactylus vilarsi, a common lowland species, is redescribed on the basis of additional specimens from southern Venezuela.